Data Hiding Method Based on Graph Coloring and Pixel Block‘s Correlation in Color Image - G. Ghadimi; M. Nejati Jahromi; E. Ghaemi Ghaemi; A. H. Heydari (AUT Journal of Electrical Engineering, 2017)
An optimized method for data hiding into a digital color image in spatial domainis provided. The graph coloring theory with different color numbers is applied. To enhance thesecurity of this method, block correlations method in an image is used. Experimental results showthat with the same PSNR, the capacity is improved by %8, and also security has increased in themethod compared with other methods. In the correlation block-based image method, data hidingcapacity of the host image varies according to image type and defined threshold level. In theproposed algorithm, during graph explanation, independent pixels placed side by side were colored.Then, based on “pixel block correlation data hiding” process is done. This method grows thesecurity and capacity of hiding process. Besides, this increases the effects of image format andcorrelation threshold on security and capacity.